Vertebral compression fracture in CT imaging - a case study - Grzegorz Wróbel (Kazimierz Wielki University, 2018)
Compression fractures of the spine are frequent clinical problems, include damage to the vertebral bodies, leading to their collapse and reduction in height. A 67-year-old woman with symptoms of constant back pain, especially during standing and walking, the mobility of the spine was limited while lying on the back decreased the feeling of pain. As a result of the study, compression fractures of the three thoracic vertebrae were observed, this concerned Th6, Th8, Th11 vertebral bodies and in the case of the first lumbar vertebrae (L1). A computed tomography (CT) scan allows for the best imaging of bony anatomy and improved assessment of loss of height, retropulsion of fragments into the central canal.